European and Asian contribution to the genetic diversity of mainland South American chickens - Herrera, M.B.; Kraitsek, S.; Alcalde, J.A.; Quiróz, D.; Revelo, H.; Álvarez, L.A.; Rosario, M.F.; Thomson, V.; Han Jianlin; Austin, J.J.; Gongora, J. (Royal Society, 2020)
Chickens (Gallus gallus domesticus) from the Americas have long been recognized as descendants of European chickens, transported by early Europeans since the fifteenth century. However, in recent years, a possible pre-Columbian introduction of chickens to South America by Polynesian seafarers has also been suggested. Here, we characterize the mitochondrial control region genetic diversity of modern chicken populations from South America and compare this to a worldwide dataset in order to investigate the potential maternal genetic origin of modern-day chicken populations in South America. The genetic analysis of newly generated chicken mitochondrial control region sequences from South America showed that the majority of chickens from the continent belong to mitochondrial haplogroup E. The rest belongs to haplogroups A, B and C, albeit at very low levels. Haplogroup D, a ubiquitous mitochondrial lineage in Island Southeast Asia and on Pacific Islands is not observed in continental South America. Modern-day mainland South American chickens are, therefore, closely allied with European and Asian chickens. Furthermore, we find high levels of genetic contributions from South Asian chickens to those in Europe and South America. Our findings demonstrate that modern-day genetic diversity of mainland South American chickens appear to have clear European and Asian contributions, and less so from Island Southeast Asia and the Pacific Islands. Furthermore, there is also some indication that South Asia has more genetic contribution to European chickens than any other Asian chicken populations.